Analisis Work-Life Balance dalam Sistem Kerja Hybrid dan Remote - Stephanie Octelerintia; Sunarto Sunarto (Journal of Comprehensive Science, 2026)
The development of digital technology and changes in global work patterns have prompted organizations to adopt flexible work systems, such as hybrid and remote work. This change provides opportunities to improve employee welfare, but also poses challenges in maintaining work-life balance. This study aims to analyze the implementation of hybrid and remote work systems and their impact on employee work-life balance. Using a quantitative approach and surveys, this research identifies how thesework systems affect employees' performance, well-being, and stress management. The findings indicate that hybrid and remote work systems provide significant flexibility in managing work time and location, contributing to an improved balance between work and personal life. Thus, it can be concluded that the implementation of a flexible work system is an effective strategy in improving employees' work-life balance. Therefore, organizations need to optimize hybrid and remote work policies with the support of appropriate technology and management to improve employee well-being and productivity. This study also provides strategic recommendations for organizations to optimize flexible work policies to support employee well-being.